A Diversity Mindset Perspective on Inclusive Leadership. Issue 4 (August 2022) - van Knippenberg, Daan; van Ginkel, Wendy P.
Team diversity research has established that diversity has the potential to stimulate synergetic performance outcomes through information integration processes, but also has the potential to invite interpersonal tensions that disrupt the very information integration process that can give more diverse teams an advantage over more homogeneous teams. A focus on the role of team leadership in stimulating information integration processes and preempting interpersonal tensions is obvious and important, but surprisingly underdeveloped conceptually and empirically. In this article, we integrate insights from two complementary perspectives on leadership and diversity—inclusive leadership and leadership for diversity mindsets—to advance a more integrative perspective on how team leadership can stimulate both inclusion and synergy from diversity.